The impact of privatisation on wages : evidence from the Portuguese banking industry - Monteiro, Natália (2004)
We present quasi-experimental estimates of the effect of privatisation on wages in the Portuguese banking sector for the period 1989-97. The design of the reform and the nature of dataset employed provide an important opportunity to analyse the effects of privatisation on different demographic groups, using multiple control groups and taking into consideration the timing of the effects. We find a positive relationship between time of restructuring and wage variation regardless the choice of the control group. Retained employees in privatised firms did experience lower wage growth rates, but only during the first two years after the ownership change. Estimates for top managers appear to contradict the theoretical predictions.